SECURE EDGE DOMINATION AND VERTEX EDGE DOMINATION IN INTUITIONISTIC FUZZY GRAPHS - KARUNAMBIGAI, M. G.; SIVASANKAR, S.; PALANIVEL, K. (International Journal of Mathematical Archive, 2018)
In this paper, we introduce the concept of secure edge domination and inverse secure edge domination of an intuitionistic fuzzy graph (IFG). The relationship between edge domination numberÂ and inverse secure edge domination number is studied. Also, we introduce a total secure edge dominating set, inverse total secure edge dominating set and vertex edge dominating set in intuitionistic fuzzy graph with suitable illustrations.